Advances in Computed Tomography Evaluation of Skull Base Diseases - Prevedello,Luciano M. (2014)
Introduction Computed tomography (CT) is a key component in the evaluation of skull base diseases. With its ability to clearly delineate the osseous anatomy, CT can provide not only important tips to diagnosis but also key information for surgical planning. Objectives The purpose of this article is to describe some of the main CT imaging features that contribute to the diagnosis of skull base tumors, review recent knowledge related to bony manifestations of these conditions, and summarize recent technological advances in CT that contribute to image quality and improved diagnosis. Data Synthesis Recent advances in CT technology allow fine-detailed evaluation of the bony anatomy using submillimetric sections. Dual-energy CT material decomposition capabilities allow clear separation between contrast material, bone, and soft tissues with many clinical applications in the skull base. Dual-energy technology has also the ability to decrease image degradation from metallic hardwares using some techniques that can result in similar or even decreased radiation to patients. Conclusions CT is very useful in the evaluation of skull base diseases, and recent technological advances can increase disease conspicuity resulting in improved diagnostic capabilities and enhanced surgical planning.